2020
DOI: 10.1073/pnas.1915681117
|View full text |Cite
|
Sign up to set email alerts
|

TRMintegrins CD103 and CD49a differentially support adherence and motility after resolution of influenza virus infection

Abstract: Tissue-resident memory CD8 T (TRM) cells are a unique immune memory subset that develops and remains in peripheral tissues at the site of infection, providing future host resistance upon reexposure to that pathogen. In the pulmonary system, TRMare identified through S1P antagonist CD69 and expression of integrins CD103/β7 and CD49a/CD29(β1). Contrary to the established role of CD69 on CD8 T cells, the functions of CD103 and CD49a on this population are not well defined. This study examines the expression patte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 53 publications
4
71
2
Order By: Relevance
“…This finding has clinical implications as it affects the development of psoriasis, and it also demonstrates how sequestration of cells in tissue locales can occur based on integrin expression ( 67 ). Similarly, CD103 + (αE + ) T cells are found within lung epithelium, suggesting that αE can be considered a marker of epithelial localization that correlates with expression of E-cadherin by epithelial cells lining the alveoli and basement membrane ( 201 , 202 ). While the localization of trNK cells in the lung has not been well-defined, it is likely that the distinct populations found here are also spatially distinct, with CD103 marking a population found in the epithelium (discussed further below and summarized in Figure 3 ).…”
Section: Trnk Integrin Expression In Humansmentioning
confidence: 99%
“…This finding has clinical implications as it affects the development of psoriasis, and it also demonstrates how sequestration of cells in tissue locales can occur based on integrin expression ( 67 ). Similarly, CD103 + (αE + ) T cells are found within lung epithelium, suggesting that αE can be considered a marker of epithelial localization that correlates with expression of E-cadherin by epithelial cells lining the alveoli and basement membrane ( 201 , 202 ). While the localization of trNK cells in the lung has not been well-defined, it is likely that the distinct populations found here are also spatially distinct, with CD103 marking a population found in the epithelium (discussed further below and summarized in Figure 3 ).…”
Section: Trnk Integrin Expression In Humansmentioning
confidence: 99%
“…In support of this view, depletion of CD49a results in a decrease of memory T cells within the lung [59]. However, a recent study has shown that CD49a expression on T cells facilitates locomotion of virus specific CD8 + T cells in the trachea, suggesting that CD49a supports T RM motility in this organ [63].…”
Section: T Rm Cell Development and General Featuresmentioning
confidence: 89%
“…This protein, also known as integrin α1, pairs with CD29 (integrin β1) to form the very late antigen (VLA-1), which binds to extracellular collagen and laminin and promotes the retention of T cells in tissues [59]. In peripheral tissues, like skin or liver, the majority, but not all, of murine and human T RM cells express CD49a [3,48,[60][61][62][63]. Importantly, in human skin, CD49a expression has been shown to discriminate two functionally different populations of T RM cells, with CD49a + T RM cells producing IFN-γ and CD49a -T RM cells producing IL-17 [64].…”
Section: T Rm Cell Development and General Featuresmentioning
confidence: 99%
“…CD103 may be targeted directly via specific antibodies or by modulating TGF-β signaling, which induces CD103 expression on T cells. Using anti-CD103 and anti-CD49a blocking antibodies, knockout mice, and intravital imaging, Reilly and colleagues showed that CD103 and CD49a differentially support adherence and motility of virus-specific T cells after the resolution of an influenza virus infection [ 71 ]. Moreover, enhancing CD103 expression on mucosal T cells by targeting DC-dependent activation of TGF-β has been shown to inhibit tumor progression in a preclinical model of breast cancer [ 72 ].…”
Section: Functional Heterogeneity and Therapeutic Targetingmentioning
confidence: 99%